Rancang Bangun Lampu LED 12 Volt DC Dengan Rangkaian Penggerak Berbasis Topologi Flyback - Yakub Jonathan; Budhi Anto; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Driving circuit function as a source of voltage to drive an electronic circuit. Source of voltage (power supply) created using the switching mode with Flyback converter topology. Component used as the switch is Mosfet. Time to live (on) and off (off) controlled by the circuit mosfet Totempole to accelerate the process on or off of the switch with a frequency of 50 kHz generated by IC SG3524. Switching mode power supply with Flyback converter topology are made to produce a constant voltage of 87 volts. Input source that will be used is lead acid batteries 12 Volt supplies 78 pieces LED.Keywords: Flyback Converter, circuit Totempole, Mosfet IR540, LED, IC SG3524, Switching Power Supply